DOI: 10.11606/t.17.2018.tde-10042018-150836
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação quantitativa e qualitativa da densidade de transportadores pré-sinápticos de Dopamina em pacientes saudáveis e em portadores de Doença de Parkinson: um estudo de SPECT com [99mTc]-TRODAT-1

Abstract: accurate was the manual, followed by Two Box. The manual method would potentially reduce false positive cases from 3 to 0 and false negative cases from 9 to 7. The reproducibility of semiquantitative methods was excellent. In general, negative correlations between striatal DAT binding and PD severity and motor scales were found, however, the correlations were not statistically significant. Asymmetry index and putamen/caudate ratio presented inferior performance compared to BPI. A statistically significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 42 publications
(60 reference statements)
1
7
0
5
Order By: Relevance
“…These results were similar to those found by Pagano et al [ 13 ] with 61.6 ± 9.7 for PD and by Tzen et al [ 15 ] with 70 ± 7.5 for VP. We believe that these differences in age and gender between the Parkinsonism did not influence the differences obtained in the SPECT-TRODAT results because most studies with PET-CT and SPECT have not shown statistically significant differences between changes in DAT uptake concerning sex [ 13 , 14 , 28 – 32 ]. Moreover, DAT/SPECT uptake rates in healthy patients are stable between 30 and 70 years of age, allowing someone around 70 years of age to have SPECT-TRODAT results similar to another 30-year old [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results were similar to those found by Pagano et al [ 13 ] with 61.6 ± 9.7 for PD and by Tzen et al [ 15 ] with 70 ± 7.5 for VP. We believe that these differences in age and gender between the Parkinsonism did not influence the differences obtained in the SPECT-TRODAT results because most studies with PET-CT and SPECT have not shown statistically significant differences between changes in DAT uptake concerning sex [ 13 , 14 , 28 – 32 ]. Moreover, DAT/SPECT uptake rates in healthy patients are stable between 30 and 70 years of age, allowing someone around 70 years of age to have SPECT-TRODAT results similar to another 30-year old [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seeking an earlier diagnosis, preferably in the premotor phase of PD, the valorization of NMS as clinical biomarkers is occurring, especially in conjunction with imaging, genetic, or biochemical biomarkers [ 1 , 29 ]. The ease in analyzing the images obtained by SPECT-TRODAT, by visual inspection, allows a well-trained neurologist to correlate them with the neurological examination findings [ 8 , 9 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations